Impact of on-site compared to off-site testing for severe acute respiratory coronavirus virus 2 (SARS-CoV-2) on duration of isolation and resource utilization. (24th August 2021) - Roberts, Andrew T.; Wong, Gabriella; Kotsanas, Despina; Francis, Michelle J.; Stuart, Rhonda L.; Graham, Maryza; Rogers, Benjamin A.
Abstract: Rapid detection and isolation of coronavirus disease 2019 (COVID-19) patients is the only means of reducing hospital transmission. We describe the impact of implementation of on-site severe acute respiratory coronavirus virus 2 (SARS-CoV-2) reverse-transcription polymerase chain reaction (RT-PCR) testing on reducing turnaround time, isolation duration, pathology test ordering, and antibiotic use in patients who do not have COVID-19.